Comparatively Queer
IX, 234 p.
Keywords: These innovative essays take a comparative approach to queer studies while simultaneously queering the field of comparative literature, strengthening the interdisciplinary of both. The book focuses not only on comparative praxis, but also on interrogating our assumptions and categories of analysis.